Harnessing Managerial Knowledge to Implement Product-Line Extensions: How do Mutual Fund Families Allocate Portfolio Managers to Old and New Funds? - Drazin, Robert; Rao, Hayagreeva (Academy of Management Journal, 2002)
Building on the knowledge-based view of the firm, we examine the effects of experience and complexity on decisions to staff product-line extensions with shared or dedicated managers. Results suggest that new and old product lines are more likely to share a manager when the organization possesses a base of knowledge related to the extension and when the new product is low in complexity. These results extend understanding of knowledge and product platforms by focusing on implementation and resource deployment.